Congenital Ichthyosis in 14 Great Dane Puppies With a New Presentation. (May 2016) - Hoffmann, A.; Metzger, J.; Wöhlke, A.; Peters, M.; Junginger, J.; Mischke, R.; Distl, O.; Hewicker-Trautwein, M.
The present study describes a generalized congenital skin condition in 14 Great Dane puppies. Macroscopically, all dogs showed generalized gray to yellow scaling and skin wrinkles on the head and all 4 extremities. Skin sections were histologically examined using hematoxylin and eosin, Heidenhain's Azan, and Sudan red III staining methods and by conducting the alcian blue/periodic acid Schiff (AB/PAS) reaction technique on sections. Furthermore, incubation with hyaluronidase was performed. Skin samples were ultrastructurally analyzed using transmission electron microscopy. All affected Great Dane puppies had epidermal and follicular orthokeratotic hyperkeratosis, enlarged keratohyaline granules, vacuolated keratinocytes, and accumulations of an eosinophilic and alcianophilic, lipid-rich material within dilated hair follicular lumina and the cytoplasm of sebocytes. The macroscopic, histopathologic, and ultrastructural skin changes in all 14 Great Dane puppies indicate a new variant of a primary disorder of cornification with congenital, non-epidermolytic, lamellar ichthyosiform appearance.